A NEW APPROACH TO CREATING A HIGHLY STABLE RANGE MICROWAVE GENERATOR - BILYK, Oleksandr; KONONOV, Serhii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A range microwave generator is considered. A frequency multiplier is installed in the PLL loop of the generator. There is no frequency divider in the generator. It has increased stability due to low output phase noise. The proposed device can be used in telecommunications and radio equipment. The microwave generator consists of an autogenerator, three multipliers, a bandpass filter, two low-pass filters, a reference frequency unit, a harmonic generator, and a control unit. Auxiliary units of the generator are two adders, a key and two controllers. The first multiplier together with the bandpass filter works as a stroboscopic transducer, the second - as a quadrator, the third with a low-pass filter - as a phase detector. The inputs of the stroboscopic converter receive two voltages from the harmonic generator. The frequencies of the first voltage harmonics are close. Voltages have the form of short pulses and are enriched with harmonics. After the signal at the output of the first low-pass filter, the first controller opens the key, switches the reference frequency node and through the second controller closes the PLL loop. The control unit sets the reference frequencies and changes the frequency of the autogenerator. The main nodes of the PLL loop are the third multiplier with the second low-pass filter. Auto-tuning of the generator begins with the appearance of the control signal from the quadrator. The signal appears after the strobe conversion frequency at the output of the bandpass filter coincides with the center frequency. The frequency instability of the range generator decreases. It is approaching the instability of the reference frequency. The stability of the reference frequencies determines the relative frequency error of the range of the microwave generator. The maximum frequency depends on the parameters and dynamic properties of the autogenerator, stroboscopic transducer and harmonic generator. A high-quality harmonic generator will provide a low level of phase noise. The structural scheme of the microwave generator is offered and its work is explained. The analysis of the mathematical model of the microwave generator is performed. The formulas of interrelation of voltages of knots with initial oscillation of the generator are received. Computer simulations have confirmed that the output frequency can be stabilized in the generator.
Keywords: band generator; microwave generator; frequency instability; phase noise; harmonic generator; frequency multiplier; multiplier; filter; PLL; reference frequency